The suppression of the SPHK1/S1P/S1PR3 signaling pathway diminishes EGFR activation and increases the sensitivity of non-small cell lung cancer to gefitinib - Jing Zhang; Zequn Wang; Xihua Wei; Mengyuan Han; Ribai Yan; Lijie Ma; Yan Pan (Current Research in Pharmacology and Drug Discovery)
Non-small-cell lung cancer (NSCLC) represents a predominant histological subtype of lung cancer, characterized by high incidence and mortality rates. Despite significant advancements in therapeutic strategies and a deeper understanding of targeted therapies in recent years, tumor resistance remains an inevitable challenge, leading to poor prognostic outcomes. Several studies have indicated that sphingosine kinase 1 (SPHK1) plays a regulatory role in epidermal growth factor receptor (EGFR) signaling, and its elevated expression may be associated with resistance to EGFR tyrosine kinase inhibitors (EGFR-TKIs). Furthermore, the catalytic product of SPHK1, sphingosine 1-phosphate (S1P), along with its receptor, sphingosine 1-phosphate receptor 3 (S1PR3), plays a regulatory role in the function of the EGFR. However, the specific effects of the SPHK1/S1P/S1PR3 axis on EGFR in NSCLC, as well as the combined effects of SPHK1/S1P/S1PR3 inhibitors with the EGFR-TKI gefitinib, remain to be elucidated. In the present study, we investigated the correlation between SPHK1 expression levels and the survival rates of NSCLC patients, the relationship between SPHK1 or S1PR3 and EGFR, and the impact of SPHK1 expression on the half-maximal inhibitory concentration (IC50) of gefitinib in NSCLC. In A549 cells, the phosphorylation of EGFR was significantly reduced following SPHK1 knockdown. Utilizing SPHK1/S1P/S1PR3 inhibitors, namely PF543, TY52156, and FTY720, we established that the SPHK1/S1P/S1PR3 axis modulates EGFR activation in NSCLC. Furthermore, these signaling inhibitors enhanced the anti-proliferative efficacy of the EGFR-TKI gefitinib. RNA sequencing analysis revealed substantial alterations in 85 differentially expressed genes in NSCLC cells treated with the combination of FTY720 and gefitinib. These genes were predominantly associated with pathways such as axon guidance, microRNAs in cancer, and the JAK-STAT signaling pathway, among others. Overall, targeting the SPHK1/S1P/S1PR3 signaling pathway represents a promising therapeutic strategy to enhance gefitinib sensitivity in NSCLC.